Maternal risk factors for neonatal conjunctivitis in Aminu Kano Teaching Hospital, Kano, Nigeria - Asani, Mustafa; Aliyu, Ibrahim; Also, Umar (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: Neonatal conjunctivitis remains a major cause of preventable childhood blindness in developing countries. There are maternal risk factors, which if identified can assist in its prevention.Objective: This study attempts to determine the maternal risk factors for the development of neonatal conjunctivitis among babies seen in a tertiary health facility in Kano, Nigeria.Materials and Methods: This was a cross-sectional study. Neonates from special care baby unit, postnatal ward, paediatric out-patient unit and labour room who had bilateral or unilateral eye discharge were enrolled in the study. Those neonates whose parents refused consent were excluded from the study. The questionnaire sorted for information including patients' biodata, place and mode of delivery, age at onset of eye discharge, mothers' biodata, antenatal care attendance, educational and socioeconomic status and obstetrics history. Samples were collected and Gram staining was conducted using standard technique.Chlamydialantigens were detected using a rapid immunochromatographic technique (ICT). The data were analysed using EPI INFO version 3.5.1 2002. Proportions were compared using Chi-square test of significance. A probability (P -value) of less than 0.05 was considered statistically significant.Results: A total of 175 neonates were studied. The mean age was 5.7 ± 4.6 days with a male:female ratio of 1.1:1. Low level of maternal education, lack of antenatal care attendance, prolonged rupture of amniotic membranes and low socioeconomic status were significantly associated with isolate positive neonatal conjunctivitis.Conclusion: Maternal factors including lack of antenatal care attendance and poor socioeconomic conditions are significantly associated with isolate positive neonatal conjunctivitis.
Keywords: Aminu Kano teaching hospital; congenital heart disease; down syndrome